Analysis of Islamic Religious Education Teacher Policy in the Islamic Religious Education Learning Process for Inclusive Class at Muhammadiyah High School 6 Surakarta - Wardani, Risma; Jinan, Mutohharun (Department of Special Education, 2024)
This research was motivated by observations that showed that the learning process carried out by Islamic education teachers in the learning process was less than optimal, especially in inclusive schools so educational goals were difficult to achieve. This has a big impact on special needs students and regular students so the implementation of learning is not optimal and less effective. So it can be formulated in this research that the role of teachers in maximizing learning planning, learning processes, and learning evaluation is very necessary. This research aims to analyze the Islamic Religious Education learning process to know the implications for special needs students and regular students as well as for Islamic education teachers. This study uses a qualitative method. Qualitative analysis is taken from Islamic religious education teachers' interpretation of data by providing information and explanations. Research data collection was carried out using interview techniques and field observations. The results of this research show that the relationship between policy and teacher professionalism in teaching greatly influences the continuity of learning so that it can provide changes in the implementation of learning and have an impact on students at the inclusive school Muhammadiyah High School 6 Surakarta. Teacher policies and professionalism have a high influence on the quality of learning and student development.